Nickel-Catalyzed Multicomponent Coupling Reaction of Alkyl Halides, Isocyanides and H2O: An Expedient Way to Access Alkyl Amides - Li, Qiao; Jin, Hongwei; Liu, Yunkui; Zhou, Bingwei (Synthesis, 2020)
We herein describe a Ni-catalyzed multicomponent coupling reaction of alkyl halides, isocyanides, and H2O to access alkyl amides. Bench-stable NiCl2(dppp) is competent to initiate this transformation under mild reaction conditions, thus allowing easy operation and adding practical value. Substrate scope studies revealed a broad functional group tolerance and generality of primary and secondary alkyl halides in this protocol. A plausible catalytic cycle via a SET process is proposed based on preliminary experiments and previous literature.
Keywords: nickel catalysis; isocyanide; alkyl halides; multicomponent coupling reaction; amide